Hemolytic uremic syndrome associated with paraquat intoxication. Issue 3 (25th November 2013) - Jang, Ha Nee; Bae, Eun Jin; Hwang, Kyungo; Kang, Yeojin; Yun, Seongeun; Cho, Hyun Seop; Chang, Se‐Ho; Park, Dong Jun
<x xml:space="preserve">Abstract</x> We report a case of a 66‐year‐old patient with paraquat intoxication resulting in the requirement for hemoperfusion, hemodialysis, and plasma exchange. His initial serum paraquat level was 0.24 µg/mL (0.0–0.1 µg/mL). Activated charcoal (50 g) was administered orally, and high‐dose N‐acetylcysteine (150 mg/kg) was administered intravenously. In addition, immediate 4 h hemoperfusion was also performed for three consecutive days after admission. Hemodialysis was started on the 4th day after admission because of uremia. On the 9th day after admission, laboratory findings demonstrated hemolytic uremic syndrome (HUS): microangiopathic hemolytic anemia (MAHA), thrombocytopenia, elevated reticulocyte count, and lactate dehydrogenase (LDH). Plasma exchange was performed three times consecutively. Anemia and thrombocytopenia were improved, and LDH was normalized after plasma exchange. Urine output increased to 2240 mL/day on the 18th day after admission, and hemodialysis was discontinued. He is currently being observed at our follow‐up clinic without renal impairment or pulmonary dysfunction for 1.5 years since discharge. We should suspect paraquat‐associated HUS when thrombocytopenia and anemia are maintained for a long time after paraquat intoxication. J. Clin. Apheresis 29:183–186, 2014. © 2013 Wiley Periodicals, Inc.